Evaluasi Lokasi Eksisting Halte Bus Rapid Transit Trans Jogja - Setya Adi Bawana; Rini Rachmawati (Institut Transportasi dan Logistik Trisakti, 2020)
Trans Jogja is one of the government programs to create connectivity in Yogyakarta and the existence of the bus shelter greatly influences the range of passengers which can be optimized if it is located near the housing or public area. This study aims to (a) Identify the existing locations of Trans Jogja Bus Rapid Transit (BRT) shelters in the city, (b) Identify the range of Trans Jogja Bus Rapid Transit (BRT) passengers to the existence of bus stops, and (c) Identify the realization of the Trans Jogja Bus Rapid Transit (BRT) shelters’ development in Yogyakarta. The bus shelters’ level of density is different for each distribution area. The highest level is in the residential areas and places of activity with a percentage of 46%, followed by education areas (25.5%), government (13.4%), health (7.9%), trade (3.3%), tourism (2.9%), and the developed area (0.8%). 75% of Trans Jogja BRT users come from within the range of 0-300 meters buffer of the bus stops. The bus shelters at the center of the activity will be much easier to reach and have high accessibility, in that case the distance between bus stops is closer and the density is higher. The connection between bus stops and bus stops’ planning has a degree of interconnection of 100%. It indicates that all the bus stops planned to be developed in 2017 have been built in 2019.